TCAD analysis of the high-temperature reverse-bias stress on AlGaN/GaN HEMTs - Franco Ercolano; Luigi Balestra; Sebastian Krause; Stefano Leone; Isabel Streicher; Patrik Waltereit; Michael Dammann; Susanna Reggiani (Power Electronic Devices and Components)
The long-term reliability of AlGaN/GaN high electron mobility transistors (HEMTs) is a crucial factor in their widespread adoption for high-power and high-frequency applications. Before investigating the device behavior under high-temperature reverse-bias (HTRB) conditions, a fine tuning of the TCAD simulation setup was conducted by benchmarking against measured transfer, input, and output characteristics. This calibration step ensured an accurate representation of the device electrical performance, serving as a solid foundation for further TCAD stress analysis. Subsequently, the comparison between HTRB experimental results and the calibrated TCAD simulations was carried out to understand degradation mechanisms under stress conditions. The study particularly focuses on the role of passivation/cap interface traps, which are known to influence both the drain current (ID) and gate current (IG) over time. By varying key parameters such as trap density and energy levels, the impact of these traps on device performance is consistently explored. The simulations not only corroborate experimental findings but also provide deeper insights into the physical mechanisms driving current collapse, enabling more accurate predictions of long-term device behavior under high-stress conditions. These results contribute to the ongoing development of more reliable GaN-based technologies, emphasizing the importance of interface quality and trap management.